Abdullah, Ismail. “The Impact of Reformist (Iṣlāḥī) Thought in Tafsīr (Qur’anic Exegesis) on Malayan Tafsīr Methodology: The Tafsīr al-Qur’ān al-Ḥakīm of the Malaysian Shaykh Mustafa Abdul Rahman as a Model,” Year 12, Issues 46-47 (Fall 1428 AH/ 2007 CE) - عبد الله, إسماعيل (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2007)
Ismail Abdullah’s article examines reformist views in the Qur’anic exegesis (tafsīr) of the Malaysian Shaykh Mustafa Abdul Rahman. It discusses the march towards reform in the Malay world, and the process of reform in methodologies of Qur’anic exegesis. It introduces Shaykh Mustafa Abdul Rahman and his book Tafsīr al-Qur'ān al-Karīm, and discusses the impact of reformist orientations in his methodology. It also highlights his intellectual output and reformist legacy in light of the political, cultural, and social conditions in which he lived; touching upon the effect that his upbringing and environment had on his reformist thought.